Identifying multimorbidity patterns of non-communicable diseases in paediatric inpatients: a cross-sectional study in Shanghai, China - Chen Chen; Wenya Yu; Qian Liu; Yan Yang; Liang Zhou; Jianwei Shi; Hua Jin; Zhaoxin Wang; Jiaoling Huang; Ning Chen; Xiaoxiao Shi; Zhaohu Yu (BMJ Open)
Objectives To enhance the understanding of non-communicable disease (NCD) multimorbidity in children who are inpatients by delineating the characteristics of and identifying patterns among paediatric inpatients with multimorbidity in China.Design Cross-sectional study.Setting Paediatric wards (n=17) in Pudong New Area, Shanghai, China.Participants A total of 193 432 paediatric inpatients in the electronic health record systems of 17 hospitals from 2011 to 2016 participated in the study, and 91 004 children with NCDs were extracted and classified based on International Classification of Diseases, 10th version codes.Main outcome measures Number of the NCDs and multimorbidity patterns of the paediatric inpatients.Results In total, 47.05% (95% CI 46.83 to 47.27) of the paediatric inpatients had one or more chronic diseases, and 16.30% (95% CI 16.14 to 16.46) had multimorbidity. Congenital anomalies accounted for 19.43% (95% CI 19.25 to 19.61) of the principal diagnoses among the paediatric inpatients. Five common multimorbidity patterns were identified: a neurological-respiratory cluster, a neurological-respiratory-ear cluster, a cardiovascular-circulatory cluster, a genitourinary cluster (boy group) and a musculoskeletal-connective cluster (10–18 years age group).Conclusions Multimorbidity in paediatric inpatients suggests that decisions about reasonable allocation of paediatric inpatient resources should be fully considered. Multimorbidity patterns in paediatric inpatients revealed that prevention, including innovative treatments targeting children, should be further studied.